FREQUENCY OF CAUSES OF ASCITES IN PATIENTS ADMITTED AT MEDICAL UNIT OF A TERTIARY MEDICAL CARE FACILITY - Shaikh, Mumtaz Ali; Khan, Jehangir; Almani, Suhail; Yakta, Dur -e-; Shaikh, Dargahi (Journal of Ayub Medical College Abbottabad, 2010)
Background: Ascites can be defined as accumulation of free fluid in the peritoneal cavity. It is the most common complication of cirrhosis and is associated with a poor quality of health, increased risks of infections, renal failure and a poor long-term outcome. This descriptive analytical study was conducted on one hundred and fifty diagnosed patients of ascites consecutively admitted in medical unit of tertiary care facility attached to Muhammad Medical College, Mirpur Khas, Sindh, from Oct 2006 to Sep 2008. Methods: Special proforma was prepared containing patients’ basic information, history, clinical findings and investigations necessary to diagnose the cause of ascites. Patients with ascites due to perforation and intraperitoneal bleeding were excluded from the study. Serum-ascitic albumin gradient (SAAG) was calculated and patients were grouped into high and low SAAG groups. The obtained data was analysed using SPSS-11. Results: In this study 150 patients of ascites were included. Patients were arranged in two groups. High SAAG ’˜high portal pressure’ group and low SAAG ’˜low portal pressure’ group. In high SAAG group patients included were 128 (85.33%), and in low SAAG group patients included were 22 (14.66%). In high SAAG group, out of 128 (85.33%) patients 122 (81.33%) were of cirrhotic ascites, [(viral hepatitis B, C and combined 105 (70%), alcoholic 7 (4.66%), cryptogenic 10 (6.66%)], heart failure ascitic patients were 5 (3.33%), and constrictive pericarditis 1 (0.66). In low SAAG group out of 22 (14.66%) patients malignant ascites was (primary peritoneal carcinomatosis and metastasis) 11 (7.33%), tuberculous ascites was 10 (6.66%), and ascites due to nephrotic syndrome was 1 (0.66%). Conclusion: As large number of cases of ascites are due to cirrhosis of liver that has little or no cure in developing countries. Media and NGO’s should further work to increase awareness of this deadly problem. Keywords: Ascites, SAAG, cirrhosis